THE EFFECT OF USING REAP (READ, ENCODE, ANNOTATE PONDER) METHOD ON STUDENTS’ READING COMPREHENSION IN ANALYTICAL EXPOSITIONTEXT OF THE ELEVENTH GRADEOF SMK SWASTA HARAPAN STABAT IN ACADEMIC YEAR 2019/2020 - Deden Riansyah; Nudia Yultisa (STKIP Budidaya Binjai, 2020)
The objective of this research was to find out whether there was a significant effect of using REAP (Read, Encode, Annotate, Ponder) on students’ reading comprehension in analitycal exposition text of the eleventh grade of SMK Swasta Harapan Stabat in academic year 2019/2020. In this research, the researcher took 80 students as the sample. As the experimental class, the researcher used class XI.1 ADP which consisted of 40 students and for the control class, the researcher used class XI.4 ADP that consist of 40 students. The, the researcher gave pre-test and post-test to both classes.The researcher then statistically analyzed the data by using t-test. After analyzing the data, the researcher concluded that teaching analytical exposition text using REAP method was effective. As the fact, the result of t-test was 2,86 with df = 78. Because there was not df 78 in the t-table, so the researcher decided to use df 60 since it is closer to 78 than df 120.The table at df 60 showed that the value of t-table ( was 2,00 for 5% and 2,66 for 1%. Theoritically, the Alternative Hypothesis ( ) was accepted if the value of t-test was greater than the value of t-table ( > ( . The finding showed that t-test was greater than t-table (2,86 > 2,00 and 2,66). The researcher meant the hypothesis ( ) was accepted. It was stated that “There is a significant effect of using REAP method on students’ reading comprehension in analytical exposition text of the eleventh grade students of SMK Swasta Harapan Stabat in academic year 2019/2020” was accepted.